2017
DOI: 10.1186/s13063-017-1826-6
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Shoulder Arthroplasty for the treatment of Proximal humeral fractures in the Elderly (ReShAPE trial) : study protocol for a multicentre combined randomised controlled and observational trial

Abstract: BackgroundProximal humeral fractures are common in older patients. The majority are minimally displaced and are associated with good outcomes after nonoperative treatment. Poorer outcomes are associated with displaced, multipart fractures. There is no clear benefit from surgical fracture fixation compared to nonoperative treatment. Replacement of the fractured humeral head with a hemiarthroplasty is another treatment option, but has not been shown to be clearly superior to nonoperative treatment or internal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Currently, it is common to perform primary reversed fracture arthroplasty in three- and four-part fractures with a cutoff age of 75 years [ 50 , 51 ]. For complex fractures, this procedure is performed in patients aged 65 years and up (surgeon’s observation).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is common to perform primary reversed fracture arthroplasty in three- and four-part fractures with a cutoff age of 75 years [ 50 , 51 ]. For complex fractures, this procedure is performed in patients aged 65 years and up (surgeon’s observation).…”
Section: Discussionmentioning
confidence: 99%
“…These results should be validated by a randomized prospective study, one of which is in progress by the authors. 46…”
Section: Resultsmentioning
confidence: 99%
“…Due to these disadvantages of the anatomical prosthesis, reverse shoulder arthroplasty is favoured by an increasing number of authors in complex humeral fractures, particularly for patients older than 70 years. In the last years, more and more authors reported clinical results using reverse shoulder endoprosthesis for comminuted humeral head fractures as a means to prevent complications due to tuberosity malunion and secondary rotator cuff insufficiency [9] [33]. Although this procedure provides adequate pain relief, functional outcome respectively range of motion is not always satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Although this procedure provides adequate pain relief, functional outcome respectively range of motion is not always satisfactory. Given implant failure, salvage procedures for reverse arthroplasty remain limited [33]- [38]. But functional outcome was reported to be more favourable than that of hemiarthroplasty by several authors [13] [38].…”
Section: Discussionmentioning
confidence: 99%